It is not the same blue: A comparative LCA study of blue hydrogen supply network pathways - Dana Alghool (10340691) (2024)
Blue hydrogen (H2) serves as a pivotal initial step towards emissions reduction and a seamless transition to green hydrogen by providing a cleaner alternative to grey hydrogen. Blue H2 can be obtained through diverse pathways (i.e., distinct processes and stages) within the hydrogen supply network (HSN), resulting in varying greenhouse gas emission levels. This paper uses the Life Cycle Assessment methodology to compare 18 different blue HSN pathways. Blue hydrogen is produced from three different processes (i.e., Steam Methane Reforming (SMR), Partial Oxidation of Methane (POM), and Auto-Thermal Reforming (ATR)) that are coupled with carbon capture unit (CCU). Moreover, it can be conditioned to different states or carriers (i.e., liquefied H2 , compressed H2 , ammonia, and methanol), stored using various methods, transported by different means according to its state, and reconditioned to its original state at end-users. The LCA results indicate that the NH 3 pathway has the least environmental impact measuring just 2.12 kgCO2equ/ kgH2 compared to the other 18 blue HSN pathways. This pathway involves producing hydrogen from ATR process coupled with CCS, and eventually delivering as ammonia to consumers. Additionally, the blue H2 results of this paper are compared to the green H2 results discussed in the previous paper. The comparison highlights that integrating renewable energy in the form concentrated photovoltaic collectors produces the lowest emissions compared to all pathways. It reduces the emissions from 45.3% to 67% depending on the pathways, compared to the ATR process coupled with CCU. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2024.07.165